An Analysis of the Role of Village-Owned Enterprises (BUMDes) in Promoting Community Economic Empowerment in Padangsidimpuan City: A Da'wah Perspective - Masrul Efendi Umar Harahap; Esli Zuraidah Siregar; Khoirul Anwar (Yayasan Darussalam Bengkulu, 2026)
This study aims to analyze the role of Village-Owned Enterprises (BUMDes) in economic empowerment in Padangsidimpuan City and its implementation from an Islamic perspective. As a village economic institution, BUMDes has a strategic function in improving community welfare through the management of local potential, job creation, and increasing community income. This research employs a qualitative approach with data collected through observation, interviews, and documentation. The findings reveal that BUMDes in Padangsidimpuan City plays an important role in the development of micro-enterprises, the management of local resources, and improving community access to business capital. However, several challenges remain, including limited human resources, lack of business innovation, inadequate management capacity, and low community participation. Therefore, strategies are needed to strengthen institutional capacity, enhance the skills and competencies of BUMDes managers, and increase government policy support to optimize the role of BUMDes in community economic empowerment. From a da'wah perspective, BUMDes activities reflect Islamic values such as mutual assistance (ta'awun), justice ('adl), and prosperity (falah).